Investigation of Mechanical Properties of Concrete Containing Liquid Silicone Rubber Under Axial Loads - Alireza Khaloo; Yaser Parvin darabad (Shock and Vibration)
As the experts who have taken for granted the merits of utilizing the concrete as the most common material in the structural industry, there is a need to take affirmative steps to enhance the concrete’s weaknesses such as the low ductility and energy absorption capacity. One possible way to improve the mechanical properties of concrete is to add liquid silicone rubber to the concrete. Silicone rubber is an elastomer (rubber-like material) composed of liquid rubber polymer and its hardener which is widely used in voltage line insulators, automotive applications, and medical devices. In order to increase the ductility and energy absorption of concrete, the liquid silicone rubber replaced a portion of mineral aggregates in concrete. HSRC (hybrid silicone rubber concrete) is a mixture of liquid silicone rubber with fresh concrete that liquid silicone rubber after 24 hours becomes a flexible solid rubber with low strength. In this paper, liquid silicone rubber was used to replace 0%, 2%, 4%, 8%, 12.5%, 25%, and 50% of the total mineral aggregate’s volume in concrete. Standard specimens were fabricated and tested. The fresh HSRC exhibited acceptable workability and lower unit weight compared to ordinary plain concrete. The uniaxial compressive strain-control test was conducted on the hardened HSRC specimens to obtain the complete stress-strain curve. The results showed that, with the increase of liquid silicone rubber in concrete, the amount of compressive strength, splitting tensile stress, and elastic modulus decreased. It was also observed that the percentage of reduction in compressive strength was greater than the percentage of reduction in tensile strength. Increasing silicone rubber concentration in HSRC changes the brittle mode of failure to ductile that demonstrated using nonlinearity indices. Unlike plain concrete, the failure state in HSRC occurs gently and uniformly and does not cause so much separation in the specimens. Larger deformation and higher toughness indices were obtained, when the silicone rubber concentration was increased.